Carcass variables and chemical composition of commercial broiler chickens and the red jungle fowl - Soesanto, Iman Rahayu Hidayati; Idrus, Zulkifli; M. P. K. Menon, M. K. Vidyadaran; Alimon, Abdul Razak; Babjee, Shaik Mohamed Amin (Asian-Australasian Association of Animal Production Societies, 2008)
The carcass characteristics and composition of both male and female commercial broiler chickens (CB) and the red jungle fowl (RJF) were compared at a common body weight of 800±25.6 g. The RJF and CB were 133 and 17 d of age, respectively, when they reached 800 g. The yields of breast and thigh portions and their muscle to bone ratios were higher for RJF as compared to CB. On the other hand, the latter had significantly greater hearts, livers and gizzards. The weights of the whole thigh and drumstick, and their muscles were lower in females than males. The CB had more abdominal fat than RJF. While sex had no significant effect on the absolute weights of abdominal fats in CB, the female RJF were fatter than their male counterparts. The fat and cholesterol contents of the breast and leg muscles of CB were significantly higher than those of RJF. The opposite was noted for protein content of both muscles. The effect of sex on fat and cholesterol contents varied according to muscle type. Comparison of CB and RJF at a common body weight suggested that the rate of development of body components have changed concomitantly with selection for rapid growth in the former.